Application and Limitations of Nanocasting in Metal-Organic Frameworks - Malonzo, Camille D.; Wang, Zhao; Duan, Jiaxin; Zhao, Wenyang; Webber, Thomas E.; Li, Zhanyong; Kim, In Soo; Kumar, Anurag; Bhan, Aditya; Platero-Prats, Ana E.; Chapman, Karena W.; Farha, Omar K.; et al. (AMER CHEMICAL SOC, 2018)
Nanocasting can be a useful strategy to transfer the catalytic metal clusters in metal-organic frameworks (MOFs) to an all-inorganic support such as silica. The incorporation of silica in the MOF pores as a secondary support has the potential to extend the application of the highly tunable metal-based active sites in MOFs to high temperature catalysis. Here, we demonstrate the applicability of the nanocasting method to a range of MOFs that incorporate catalytically attractive hexazirconium, hexacerium, or pentanickel oxide-based clusters (UiO-66, (Ce)UiO-66, (Ce)UiO-67, (Ce)MOF-808, DUT-9, and In- and Ni-postmetalated NU-1000). We describe, in tutorial form, the challenges associated with nanocasting of MOFs that are related to their small pore size and to considerations of chemical and mechanical stability, and we provide approaches to overcome some of these challenges. Some of these nanocast materials feature the site-isolated clusters in a porous, thermally stable silica matrix, suitable for catalysis at high temperatures; in others, structural rearrangement of clusters or partial cluster aggregation occurs, but extensive aggregation can be mitigated by the silica skeleton introduced during nanocasting.
Keywords: ATOMIC LAYER DEPOSITION; CATALYTIC-ACTIVITY; ACTIVE-SITES; DEHYDROGENATION; OXIDES; UIO-66; INDIUM; NODES; STRATEGY; CLUSTERS